Conversion Chemotherapy for Technically Unresectable Colorectal Liver Metastases: A Retrospective, STROBE-Compliant, Single-Center Study Comparing Chemotherapy Alone and Combination Chemotherapy With Cetuximab or Bevacizumab. Issue 20 (May 2016) - Basso, Michele; Dadduzio, Vincenzo; Ardito, Francesco; Lombardi, Pasquale; Strippoli, Antonia; Vellone, Maria; Orlandi, Armando; Rossi, Sabrina; Cerchiaro, Eleonora; Cassano, Alessandra; Giuliante, Felice; Barone, Carlo
Abstract : Abstract: The response rate of patients with unresectable liver-limited metastases of colorectal cancer can be improved by converting inoperable disease to operable disease. However, the benefits of conversion chemotherapy for survival are still controversial. Patients considered to have technically inoperable disease by a multidisciplinary team were retrospectively analyzed. Patients were stratified based on the treatment they received, into the chemotherapy only (G1), chemotherapy plus bevacizumab (G2), or chemotherapy plus cetuximab (G3) groups. The primary endpoint was the resection rate. The secondary endpoint was the overall survival (OS), according to both the treatment received and liver surgery status. In total, 104 patients were included: 30 in the G1, 39 in the G2, and 35 in the G3 groups. All G3 patients had the wild-type KRAS exon 2. The surgical resection rates for patients in the G1, G2, and G3 groups were 43.3% (13/30), 30.7% (12/39), and 51.4% (18/35), respectively. Disease-free survival did not show significant differences among the 3 groups. The median OS was 35.2 months in the G1, 28.8 months in the G2, and 42.1 months in the G3 ( P = 0.25) groups. The OS was significantly higher in patients who underwent surgical resection than those who did not. The median OS was 28.4 months in patients who did not undergo resection, whereas it had not been reached after a median follow-up period of 37.5 months for patients who underwent surgical resection (events: 21/43). Our data confirmed that the conversion of initially inoperable disease to operable disease conferred a survival benefit, even in patients who relapsed after surgery. The addition of cetuximab to chemotherapy improved the objective response and resection rates, conferring a potential survival benefit even in patients whose diseases were not converted to operable disease, compared to chemotherapy alone or in combination with bevacizumab.